Isotopic source analysis of nitrogen-containing aerosol: A study of PM2.5 in Guiyang (SW, China) - Tian, Jing; Guan, Hui; Zhou, Yunhong; Zheng, Nengjian; Xiao, Hongwei; Zhao, Jingjing; Zhang, Zhongyi; Xiao, Huayun (The Science of the total environment, 2021)
The source of fine particulate matter (PM2.5) has been a longstanding subject of debate, the nitrogen-15 isotope (δ15N) has been used to identify the major sources of atmospheric nitrogen. In this study, PM2.5 samples (n = 361) were collected from September 2017 to August 2018 in the urban area of Guiyang (SW, China), to investigate the chemical composition and potential sources of PM2.5. The results showed an average PM2.5 of 33.0 μg m−3 ± 20.0 μg m−3. The concentration of PM2.5 was higher in Winter, lower in Summer. The major water resolved inorganic ions (WSIIs) were Ca2+, NH4+, Na+, SO42−, NO3−, Cl−. Nitrogen-containing aerosols (i.e., NO3− and NH4+) suddenly strengthened during the winter, when NO3− became the dominant contributor. Over the sampling period, the molar ratio of NH4+/(NO3− + 2 × SO42−) ranged from 0.1 to 0.9, thus indicating the full fixation of NH4+ by existing NO3− and SO42− in PM2.5. The annual value of NOR was 0.1 while rised to 0.5 in Winter. The variations of NOR (Nitrogen oxidation ratio) (0.1–0.5) values suggest that the secondary formation of NO3− occurred every season and was most influential during the winter. The total particulate nitrogen (TN) δ15N value of PM2.5 ranged from −5.9‰ to 25.3‰ over the year with annual mean of +11.8‰ ± 4.7‰, whereas it was between −5.9‰ and 14.3‰ during the winter with mean of 7.0‰ ± 3.8‰. A Bayesian isotope mixing model (Stable Isotope Analysis in R; SIAR) was applied to analyze the nitrogen sources. The modeling results showed that 29%, 21%, and 40% of TN in PM2.5 during the winter in Guiyang was due to nitrogen-emissions from coal combustion, vehicle exhausts, and biomass burning, respectively. Our results demonstrate that biomass burning was the main contributor to PM during the winter, 80% of the air mass comes from rural areas of Guizhou border, this transport process can increase the risk of particulate pollution in Guiyang. [Display omitted] •Nitrogen isotopes in PM2.5 were characterized in Guiyang.•Seven source factors were identified for PM2.5 using the SIAR model.•Source of biomass burning played a pivotal role in PM2.5 during winter.